Communication Challenges for Foreign Students Studying in English in a Non-English Academic Environment - Grebliauskienė, Beata (Information & Media, 2019)
Recently, education has become a global industry driven by students who have decided to study abroad. Trends show that more and more students choose to study at universities abroad for one reason or another. The growing number of international students also means a growing number of different cultures in a classroom. Cultural diversity is a highly complex phenomenon that influences the process of learning and teaching with its elements and has both positive and negative effects.The challenges faced by students with different cultural backgrounds, their impact on learning processes and academic achievements are of interest to researchers. But it should be noted that this type of research is mostly carried out in universities, where both local and foreign students study in the same language and operate in the same linguistic and cultural environment. However, an increasing number of universities operating in a local cultural and linguistic environment offer study programs abroad (mostly in English). And these organizations, as far as foreign students, face unique problems.The results of the qualitative research show that foreign students studying in such programs face both similar andunique challenges compared to studies in universities in English-speaking countries.
Keywords: intercultural communication; studies in foreign language; foreign students; communication barriers